The Integration of Islamic and Modern Sciences at UIN Malang: Contributions to the Global Knowledge Landscape - Sintya Rahmadewi; Ikhwanul Habib; Hadi Masruri; Muhibbuddin S (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This study explores the implementation of the scientific integration model at UIN Maulana Malik Ibrahim Malang, which seeks to eliminate the dichotomy between general science and Islamic science within the university's educational, research, and community service frameworks. The primary objective is to analyze both the conceptual and operational aspects of scientific integration through a qualitative-descriptive approach using literature study. Data were obtained from books, journal articles, research reports, and educational policy documents, particularly from the last decade, and were analyzed thematically. Findings reveal that UIN Malang applies a unique integration model symbolized by the "tree of knowledge," where Islamic sciences serve as the foundation and general sciences form the branches. This model is operationalized through an integrated curriculum, inductive-deductive teaching strategies, and institutional policies that position the Qur'an and Sunnah as epistemological sources for all disciplines. The study contributes theoretically to the discourse of integrative education and practically offers a replicable model for other Islamic higher education institutions aiming to produce graduates with both intellectual excellence and spiritual integrity rooted in moderate Islamic values.